1988
DOI: 10.1210/endo-123-3-1511
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical Demonstration of Estrogen and Progesterone Receptors in Muscle Cells of Uterine Arteries in Rabbits and Humans*

Abstract: Modifications of uterine blood flow are implicated in many important aspects of reproductive physiology and in several of their pathological disorders. These modifications are hormonally regulated but remain poorly understood, and various complex mechanisms have been proposed. The aim of this study was to investigate the presence and some characteristics of estrogen receptors (ER) and progesterone receptors (PR) in uterine blood vessels. Using monoclonal antibodies and immunocytochemistry we observed the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0
2

Year Published

1992
1992
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(67 citation statements)
references
References 41 publications
6
59
0
2
Order By: Relevance
“…ER has been visualized, using immunocytochemistry, in rat aortic smooth muscle cells (Orimo et al 1993) and in guinea pig, rabbit and human uterine arteries (Perrot-Applanat et al 1988, Leiberman et al 1990. In some other vascular segments, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…ER has been visualized, using immunocytochemistry, in rat aortic smooth muscle cells (Orimo et al 1993) and in guinea pig, rabbit and human uterine arteries (Perrot-Applanat et al 1988, Leiberman et al 1990. In some other vascular segments, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…ods for studying the progesterone receptor in sections of paraffin-embedded tissue. Perrot-Applanat et al (16) have further examined the immunocytochemical localization of progesterone receptors in frozen sections from human breast tumors with a monoclonal antibody to this receptor and demonstrated that the progesterone receptors are accumulated in tumor cell nuclei. In this article we describe our results whichdemonstrate estradiol, progesterone and progesterone receptors in routine paraffinsections of human salivary glands and salivary adenoid cystic carcinomas, using an indirect immunoperoxidase technique.…”
mentioning
confidence: 99%
“…It is known that blood vessels express functional PgR (Perrot-Applanat et al 1988), which would be regulated by Pg as well as by synthetic progestins, like MPA (Sitruk-Ware 2000). The involvement of PgR in cellular and molecular effects of MPA and Pg at the vascular level has been reported.…”
Section: Discussionmentioning
confidence: 99%